Siblings with congenital ichthyosis – A case report - Vinaya Ajaykumar Singh,; Ravi Toka,; Poonam Wade,; Sushma Malik, (Indian Journal of Child Health, 2021)
Ichthyosis is a disorder of cornification characterized clinically by patterns of scaling and histopathological features of hyperkeratosis. Harlequin ichthyosis (HI) is caused by mutations in the ABCA12 gene which is responsible for the development of a normal skin barrier. Babies with HI have characteristic clinical features such as markedly thickened, cracked, and ridged skin forming horny armor-like plates over the entire body. This causes facial disfigurement in form of ectropion, chemosis of orbits, and fish-like mouth flat nose crumbled ears. Limb joints become fixed, digits are constricted, nails and hair may be absent. Affected patients have high morbidity and mortality due to respiratory difficulty, poor feeding, and skin infections